Employee Attendance System Using Rapid Application Development Method Based on Location Based Service - Nazara, Elvin Meiwati; Nasien, Dewi (Journal of Applied Business and Technology, 2024)
Employee attendance is the main benchmark in assessing employee performance and discipline, as well as providing important data for company management. The use of information technology, such as computers, has helped companies make decisions effectively. However, some companies face obstacles in the employee attendance process, especially in manual or finger print situations, and absence management. By utilizing GPS technology or similar LBS technology to detect employee presence. In this context, mobile technology, especially smartphones, has an important role in providing fast and accurate access to information. The RAD method is used in making application prototypes with repeated iterations, enabling fast development and efficient improvements. The aim of this research is to apply the LBS method to support absenteeism. This application allows employees to take attendance on time via their smartphones, with attendance data directly stored in the company's servers and databases. In addition, the Global Positioning System (GPS) feature allows tracking the location of employees who are on external service. It is hoped that the results of this research can help companies minimize the problem of employee absenteeism, increase the efficiency of work processes, and provide faster and more accurate access to information. The RAD and LBS methods have proven their effectiveness in overcoming absenteeism problems and speeding up work flow. Apart from that, this research also underlines the importance of employee discipline in achieving company goals.